Pengaruh Pengambilan Keputusan Lokasi Pertambangan Batu Bara terhadap Dampak Lingkungan - Acep Samsudin; Rusdi Hidayat; Amelia Dwi Lestari; Febby Dzurrotul Amaliyah; Nashrum Minallah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Selecting a mining location is a matter that is so important in determining the location of a coal mine that must be chosen by a mining company. Several factors or criteria must be considered in determining the location of a coal mine, including soil material content, determination of the UPS (Ultimate Pit Slope), size and maximum depth limitation at the end of the pit, operation, ladder/bench dimensions, geographical and geological conditions, road geometric conditions and drainage system selection depend on groundwater conditions and rainfall in the mine area. From an environmental point of view, coal mining has an impact on changing landscapes, decreasing soil fertility, threats to biodiversity, decreasing water and air quality, and environmental pollution. Once operational, mines and acid mine drainage also remain in the mining industry. Former coal mines can have positive and negative impacts on the environment related to water quality and quantity. The purpose of this study is to determine the effect of choosing a coal mining location on environmental impacts. The method used in this research is the previous research review method. In which the researcher's efforts to find comparisons, then become inspiration for further research. Then, previous research helps the researcher position the research and prove the originality of the research. Keywords Mining, coal, impact, environment